Buyer Behavioural Impact Of Electronic Word Of Mouth Among Youngsters Towards Smart Watches In Chennai City (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Tremendous growth of technology enhanced the consumers to share their opinion on the products and services they consume. The consumers are capable of analyze the information through various sources in the social media network. The social media plays a pivotal role on scattering the information on products and services. The term Electronic Word of Mouth (EWOM) refers to the process of influencing buyer through the social media. The study focuses on the factors influencing buyer behavior and evaluates the impact of electronic word of mouth on purchasing smart watches. Questionnaires were distributed to the respondents through Google form using convenience sampling method. The electronic word of mouth made by anonymous, family and friends on social media network sites have influenced on purchase intention of respondents. The EWOM are shared by unpaid user and they became organic promoter for product and services. The social media users trust the other users review and referral as the information are communicated by prior purchaser. The EWOM influence the people to buy the product and services from the various referrals shared in social media.